2003
DOI: 10.1002/sia.1507
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the repassivation behavior of aluminum and aluminum alloy exposed to chromate solutions

Abstract: This study explores the repassivation ability of a scratch in a chromate conversion coating (CCC) on aluminum alloy, AA2024-T3, and hence evaluates the theory of migration of hexavalent chromium ions from the protected surface of the aluminum alloy to the exposed surface. To confirm that protection was indeed restored by hexavalent chromium ions, the repassivation of a scratch on pure aluminum exposed to a dichromate solution was studied. This forms the simplest subsystem model of the CCC on the alloy in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…The hexavalent chromium present in the chromate conversion coating would be able to migrate to the defects in the conversion layer where it would be reduced to Cr(III), forming a protective layer on the defect. 57,60,61 However, here, the post-treatment brings also lanthanum as a corrosion inhibitor to the TCP layer, which is present on the surface and in the coating bulk as evidenced by Tof-SIMS depth profiles (Figure 2d). Rare-earth inhibitors, particularly cerium and lanthanum, are among the most studied inhibitors for replacement of hexavalent chromium.…”
Section: Discussionmentioning
confidence: 84%
“…The hexavalent chromium present in the chromate conversion coating would be able to migrate to the defects in the conversion layer where it would be reduced to Cr(III), forming a protective layer on the defect. 57,60,61 However, here, the post-treatment brings also lanthanum as a corrosion inhibitor to the TCP layer, which is present on the surface and in the coating bulk as evidenced by Tof-SIMS depth profiles (Figure 2d). Rare-earth inhibitors, particularly cerium and lanthanum, are among the most studied inhibitors for replacement of hexavalent chromium.…”
Section: Discussionmentioning
confidence: 84%
“…The corrosion resistivity was efficiently improved due to CrO À 4 ions forming an oxide layer on the aluminum surface. Chidambaram et al [2] demonstrated reparation of scratches in chromate conversion coatings. A physical barrier was built by an Al-Cr complex and a repassivation of the flawed metal surface was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, "self-repairing" coatings have been devised which can respond to such damage. For example, CCCs contain a reservoir of labile chromate species that can migrate to scratches and help re-form the protective barrier 14 (Figure 15.3).…”
Section: Tribological Damagementioning
confidence: 99%